A more‐than‐human approach to bioethics: The example of digital health. (13th August 2020) - Lupton, Deborah
Abstract: Digital health technologies are often advocated as a way of helping people monitor, promote and manage their health, care for others and reduce the burden on healthcare systems. Yet these technologies have also been subject to criticism for limiting human flourishing and exacerbating socioeconomic disadvantage. Bioethical appraisals of digital health technologies tend to take a conventional risk‐benefit approach, positioning the human subject as a rational, autonomous agent who is acted on by technologies. In this paper, I present a case for adopting an alternative more‐than‐human perspective on bioethics. A more‐than‐human approach considers human‐technological assemblages and agencies as distributed, relational, situated and emergent. To illustrate the insights that this perspective can offer, I draw on the findings of four empirical projects I have conducted on people's use of digital devices and platforms used for health‐related purposes, including social media groups and online forums, mobile apps and wearable devices. I conclude with the argument that a more‐than‐human approach to bioethics can begin to incorporate a new 'zoë ethics' that can acknowledge and address the deeper affective, multisensory and relational dimensions of humans' encounters with and enactments of material things and nonhuman creatures.